2017
DOI: 10.1038/s41598-017-08905-y
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of stress in freestanding GaN crystals grown from Si substrates by HVPE

Abstract: We investigate the stress evolution of 400 µm-thick freestanding GaN crystals grown from Si substrates by hydride vapour phase epitaxy (HVPE) and the in situ removal of Si substrates. The stress generated in growing GaN can be tuned by varying the thickness of the MOCVD AlGaN/AlN buffer layers. Micro Raman analysis shows the presence of slight tensile stress in the freestanding GaN crystals and no stress accumulation in HVPE GaN layers during the growth. Additionally, it is demonstrated that the residual tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Previously, we discussed the optimal temperature to etch Si substrate in order to avoid the undesirable tensile stress between the substrate and GaN. 19,20 We found that the maximum in-plane stress can be minimized to À0.07 MPa at 1000 C being slightly compressive and allowing the implementation of Si etching. However, the uniformity of Si etching rate over 2-inch wafer surface is another important factor to obtain crack-free freestanding GaN.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previously, we discussed the optimal temperature to etch Si substrate in order to avoid the undesirable tensile stress between the substrate and GaN. 19,20 We found that the maximum in-plane stress can be minimized to À0.07 MPa at 1000 C being slightly compressive and allowing the implementation of Si etching. However, the uniformity of Si etching rate over 2-inch wafer surface is another important factor to obtain crack-free freestanding GaN.…”
Section: Resultsmentioning
confidence: 95%
“…The growth process is reported elsewhere in details. 19,20 Briey, GaN was grown at 1080 C in atmosphere pressure with V/III ratio of 20. The Si etching was performed using 200 sccm HCl gas ow at 1000 C aer the growth of a thick GaN layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they addressed that these strain-induced metallic bond states can be observed in the GaN crystals grown by MOCVD or HVPE, which contain the abundant stress and nitrogen concentration in the layer 39 . It is noticeable that Si-based FS-GaN underwent a huge tensile strain during the HVPE growth 16 . Furthermore, we also observed metallic Ga-Ga bonding in GaN template on a Si substrate, which underwent high tensile strain during the growth stage 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The FS-GaN crystals used in this study were grown from Si substrates, using an in-situ removal method by HVPE. The details of the growth process are described elsewhere 15,16 . A home-built vertical type HVPE system with an upstream HCl gas channel was used to achieve the FS-GaN crystal from a Si substrate.…”
Section: Methodsmentioning
confidence: 99%